La Revista de la Escuela Superior de Guerra "Tte Grl Luis María Campos" ; no. 586/2014 - Escuela Superior de Guerra Tte Grl Luis María Campos (Argentina) (2014)
Ejemplar: Revista de la ESG. Año 92, no. 586 (ene.-mar. 2014). 124 p.